2011
DOI: 10.1055/s-0030-1256074
|View full text |Cite
|
Sign up to set email alerts
|

What is the most reliable imaging modality for small colonic polyp characterization? Study of white-light, autofluorescence, and narrow-band imaging

Abstract: Of the imaging modalities tested, NBImag appeared to have the best overall accuracy and interobserver agreement, although not adequate for in vivo diagnosis. NBI and AFI did not have better sensitivity, specificity, or accuracy compared with WLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 25 publications
0
39
1
Order By: Relevance
“…The results of NBI without optical magnification in predicting histology are variable with authors showing an accuracy similar to that of optical magnification NBI and authors obtaining worse results [56]. Again, different definitions for a vascular pattern typical of adenoma (table 4) may account for these discrepancies.…”
Section: Nbi Without Optical Magnificationmentioning
confidence: 96%
See 3 more Smart Citations
“…The results of NBI without optical magnification in predicting histology are variable with authors showing an accuracy similar to that of optical magnification NBI and authors obtaining worse results [56]. Again, different definitions for a vascular pattern typical of adenoma (table 4) may account for these discrepancies.…”
Section: Nbi Without Optical Magnificationmentioning
confidence: 96%
“…Paggy et al [72] found similar results both in the whole group of < 10 mm polyps and in diminutive polyps. Other authors have not showed as good results [56,73]. The most recent report using the NICE classification found an accuracy of 89%, sensitivity of 98% and a NPV of 95%.…”
Section: Prediction Of Histology Of Diminutive Polypsmentioning
confidence: 96%
See 2 more Smart Citations
“…There are currently several complementary endoscopic technologies for colorectal exams: white light endoscopy (WLE), narrow-band imaging, autofluorescence imaging, and chromoendoscopy. [5][6][7] Interestingly, although the specificity and sensitivity of these endoscopic technologies have been estimated in a range of studies, 3,5,6,[8][9][10][11] no single technology has emerged as clearly superior. As such, WLE remains the gold standard and is often the "de facto" imaging modality for colorectal screening.…”
Section: Introductionmentioning
confidence: 99%